Driving the development of SMES’ entrepreneurs in the era of digitalisation: From the dynamic perspective of law enforcement in Malaysia - Irma Wani Othman; Salmah Topimin; Siti Nor Bayaah Ahmad; Haslinda Hasan (Academic Inspired Network, 2021)
This article discusses the driving of the development of small and medium enterprises in the era of digitalisation from the dynamic perspective of law enforcement. The thrust of the discussion puts the justification of digitalisation is now a necessity, not an option for traders to face the sustainability of lives affected by the Covid-19 pandemic. Based on the background of qualitative research in the form of inauguration, this article puts the perspective on the selection of contemporary issues based on secondary data content analysis methods that are the results of research journals, reports, books and online news sources. Among them are (i) preparation and readiness towards digital business, (ii) credibility of the digital business, (iii) the ‘glocal’ concept of e-Commerce as a borderless business (iv) e-Commerce orientation business incentives, and (v) youth and the working world. Digitalisation business ethics from a legal perspective associate with the surge in the issue of online fraud (scammer) during the period of the Movement Control Order (MCO), which relate with irresponsible parties take advantage by committing online fraud. Reflection on the accuracy of other acts such as (i) Trade Descriptions Act 2011 (Act 730), (ii) and Price Control and Anti-Profiteering Act 2011 (Act 732), (iii) Business Registration Act 1956, (iv) Electronic Commerce Act or known (Act 658, (v) Computer Crimes Act 1997, (vi) The Personal Data Protection Act 2010 (Act 709), and (vii) Communications and Multimedia Act 1998 are analysed and blended with current legal issues discussed. The target disposition of the thorough discussion emphasises a firm approach and action by creating special laws related to e-commerce based on the appropriateness of time changes. The enactment or reform of laws related to e-commerce enables the rights of customers and operators to be protected in the event of an unforeseen situation.